Onward Christian athletes : turning ballparks into pulpits and players into preachers - Krattenmaker, Tom, 1960- (Lanham, Md. : Rowman & Littlefield Publishers, 2010)
In Onward Christian Athletes, religion expert and commentator Tom Krattenmaker takes us behind the scenes of the conservative Christian movement to evangelize in the club house and enlist pro athletes to promote a specific brand of Christianity outside the mainstream of a religiously and politically diverse America. --from publisher description
On any Justice Sunday : evangelicals, pro sports, and the (conservative) campaign for Jesus -- A cross on the logo : representing for God in the high-drama, high-profile world of major league sports -- Faith coach : discipling athletes for a roster spot on God's team -- Winning for Jesus (but finding him in the loss column) : the tricky relationship between evangelism and sports success -- Church at the ballpark : Baseball Chapel and its exclusive theology in an age of growing religious diversity -- From Coors Field to eternity : faith days in Major League Baseball -- For God, country, and the Republican Party : the conservative politics of Jesus' pro sports warriors -- Domesticated Christianity : the political acquiescence of African American Christians in sports -- A match made in heaven--or hell : the dissonance between the values of Jesus and the values of big-time sports -- The salvation of sports : "getting it right" in an emerging new era of faith in sports.
Includes bibliographical references and index.
Keywords: Sports -- Religious aspects -- Christianity; Christian athletes -- United States; Christianity and culture -- United States